Perceived usability of local government (LG) financial statements by local councillors: comparative study of Finland and Germany. Issue 4 (3rd June 2021) - Haustein, Ellen; Lorson, Peter C.; Oulasvirta, Lasse Olavi; Sinervo, Lotta-Maria
Abstract : Purpose: This paper studies the usability of LG financial statements as perceived by local councillors. By drawing on a comparative view of two countries with different periods of accrual accounting use in the public sector, the authors investigate how local councillors assess the usability of LG financial statements in order to question accounting reform success. Determinants that influence the usability assessment are explored. Design/methodology/approach: Exploratory design: data were collected from questionnaires with 24 local councillors from five Finnish local governments (LGs) and 30 local councillors from six German LGs. An adjusted variant of the system usability scale was analysed with descriptive statistics and non-parametric group comparisons. Findings: In both countries, the usability assessment of financial statements seems to be positive, indicating a successful reform process. In Finland, where the accrual government accounting reform has had a longer time to settle in, councillors seem to assess usability only partially better than German councillors. Several determinants of the usability assessment were detected, such as size and debt level of the LG as well as local councillors' gender, political orientation and education. Generally, councillors need more assistance and training in using financial statements. Originality/value: The study is the first to conduct a quantitative assessment of the usability of LG financial statements as perceived by councillors. The system usability scale was adjusted to a public sector reporting context. The paper adopts a transnational comparative approach.